BRD4 Inhibition by AZD5153 Promotes Antitumor Immunity via Depolarizing M2 Macrophages - Li, Xi; Fu, Yu; Yang, Bin; Guo, Ensong; Wu, Yifan; Huang, Jia; Zhang, Xiaoxiao; Xiao, Rourou; Li, Kezhen; Wang, Beibei; Hu, Junbo; Sun, Chaoyang; et al. (Frontiers in Immunology, 2020)
High grade serous ovarian cancer (HGSOC) with the high recurrent rates urge for reasonable therapeutic strategies that can prolong overall survival. Tumor microenvironment (TME) discloses prognostic and prospective information of cancer, such as the expression level of PD-1 or PD-L1. However, in HGSOC, the impact of the therapies aiming at these targets remains unsatisfying. Tumor-associated macrophages (TAM) in HGSOC make up a large part amongst TME and transform between diverse phenotypes under different treatments. AZD5153 inhibiting BRD4, as a potential therapeutic strategy for HGSOC, was demonstrated to confer controversial vibration on TAMs, which shows the need to uncover its impact on TAMs in HGSOC. Therefore, we established models for TAMs and TAMs co-culturing with T lymphocytes in vitro. Via RT-PCR and flow cytometry, we find that AZD5153 resets TAMs from M2 type macrophages to M1-like macrophages, consequently, promotes pro-inflammatory cytokine secretion and thus activates CD8+ cytotoxic T lymphocytes (CTLs) in vitro. This modification occurs on MAF transcripts in TAM and modified by BRD4, which is the target of AZD5153. Importantly, the 3-D microfluid model demonstrates that AZD5153 sensitizes ovarian cancer to anti-PD-L1 therapy. Our results clarify that besides eliminating tumor cells directly, AZD5153 works as a regulator of TAM phenotype, providing a novel strategy combining AZD5153 and PD-1/ PD-L1 antibody that could benefit HGSOC patients.